2021
DOI: 10.3390/jpm11080824
|View full text |Cite
|
Sign up to set email alerts
|

Value of Strain-Ratio Elastography in the Diagnosis and Differentiation of Uterine Fibroids and Adenomyosis

Abstract: Benign uterine disorders, including uterine fibroids (UF) and adenomyosis (AM), can impact the life quality and fertility of women of reproductive age. Transvaginal ultrasound (TVUS) has long been used for their early identification, but its combined use with elastography seems to improve diagnostic accuracy of UF and AM. Thus, a prospective pilot study was conducted on 79 patients who underwent hysterectomy (25 microscopically diagnosed with AM and 53 with UF), with the aim of assessing the ability of TVUS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In our study, min and max SR values were obtained, with adenomyotic tissue being the stiffest, followed by fibromatous tissue and normal myometrium, these results being similar to the ones depicted by Liu et al and within one of our previous studies, conducted on patients with AM or UF [16,18]. Still, Liu et al reported lower numerical values, which may be explained by the differences between the manufacturers of the ultrasonography devices used [30].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, min and max SR values were obtained, with adenomyotic tissue being the stiffest, followed by fibromatous tissue and normal myometrium, these results being similar to the ones depicted by Liu et al and within one of our previous studies, conducted on patients with AM or UF [16,18]. Still, Liu et al reported lower numerical values, which may be explained by the differences between the manufacturers of the ultrasonography devices used [30].…”
Section: Discussionsupporting
confidence: 89%
“…According to literature data, SRE might be a valuable tool in the diagnosis of adenomyosis, but the appliance of SWE revealed contradictory results [9,18,19,33]. On the other hand, in the differential diagnosis of concomitantly existent uterine fibroids and adenomyosis, only SRE has proven its effectiveness so far [9,16,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3D TVUS can help evaluate the junctional zone and increase diagnostic accuracy [15,16 ▪ ,17 ▪ ]. Elastography has been proposed to help differentiate between fibroids and adenomyosis, with mixed results [16 ▪ ,18 ▪ ]. The results of recent studies investigating accuracy of different TVUS criteria are summarized in Table 1.…”
Section: Imaging Findingsmentioning
confidence: 99%